Analisis Gaya Bahasa Pertentangan pada Album Perayaan Patah Hati Babak 1 Karya For Revenge (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to analyze the Language of Conflict in the Album of Celebration of Broken Hearts Act 1 by For Revenge. The methods used in this study are descriptive methods and qualitative forms of research. The source of data in this study is in the form of a description related to the text of  the songs For Revenge in the Broken Heart Celebration Album Round 1. The data collection techniques in this study are documentary study techniques and recording techniques. The results of the research conducted on the Analysis of Opposing Language Styles in the Album of Celebration of Broken Hearts Round 1 of For Revenge There were 94 data consisting of hyperbole as many as 16 data, lithoses as many as 4 data, irony 1 data, oxymoron 10 data, satire 3 data, paradox 8 data, climax 14 data, anticlimax 7 data, sarcasm 1 data,  cynicism 7 data, silepsis and zeugma 5 data, apostrophe 8 data, hypostasis 5 data, and antiphrasis 3 data. This research can be implemented in the form of lesson plans in class X of Senior High School (SMA), even semester KD 3.17 Analyzing the elements that build poetry in the form of diction, imagery, diction, concrete words, language style, rhyme/rhythm, typography, theme/meaning (sense); in poetry) from the songs For Revenge in the Broken Heart Celebration Album Round 1.